Mobilidade de fósforo de fontes orgânicas e inorgânicas em solo arenoso - Azevedo, Rafhael Passaglia (2014)
The use of manure has become an important source of supply of nutrients to plants in family farming. However its unbalanced nutrient contents has led to the incorporation of high doses of some nutrients, exceeding the requirement of the crops, causing nutrient accumulation and leaching to deeper layers, especially in sandy soils. This study aimed to quantify the mobility of phosphorus (P) from four organic sources and one soluble inorganic source, applied in columns 20 and 40 cm long filled with a NEOSSOLO REGOLÍTICO obtained from a farm area with long history of organic fertilization, and relating it to the sorption characteristics. The samples were collected from the 0-10, 10-20, 20-30 and 30-40 cm layers. After dried and sieved, the samples were characterized according to their mineralogical, chemical and physical properties. We also determined the content of Al and Fe extracted with oxalate as well as the kinetics of adsorption and desorption isotherms. The mobility of P was determined in two experiments: 1) experiment with soil columns of 20 cm and, 2) experiment with soil columns 40 cm long. The soil of 0-10 cm depth received a single rate of organic (cattle manure, swine, goats and laying hens) or inorganic (soluble reagent PA) sources. The amount applied was based on the P contained in 8 Mg ha-1 of cattle manure. The inorganic source was applied reproducing the quantities N, P, K in the manure. After 15 days incubation, the columns were filled with the soil in sequential layers. Every day during 10 days the columns were leached with one-pore volume (PV) of saline solution (CaCl2 0.001 mol L-1) in both experiments. Each PV was divided in three aliquots that were analyzed for P concentration. Once the elution was finished, the columns were divided in 5-cm long cores and the soil analyzed for water (Pw) and Mehlich-1 (Pm) extractable P. Phosphorus drained from the 20-cm long columns, with greater losses from the inorganic source; the different behavior between organic and inorganic sources was related to the initial Pw concentration in the sources. Phosphorus did not drain from the 40 cm long columns, but P leached from the 0-20 cm layer to the 20-40 cm layer, in which we observed the greatest potential for P adsorption.